Scorpion envenomation-associated myocarditis: A systematic review. - Reza Fereidooni; Saeedreza Shirzadi; Seyyed Hamidreza Ayatizadeh; Mabrouk Bahloul; Amirali Tavangar; Seyed Alireza Zomorodian; Amirhossein Roshanshad; Ali Ardekani (Public Library of Science (PLoS), 2023)
Background Scorpion envenomation is associated with several complications. One of the most serious complications is the cardiac involvement in the form of myocarditis that remains the main reason for mortalities associated with scorpion envenomation. The present review aims to elucidate clinical and paraclinical findings associated with scorpion-related myocarditis, and to explore different management strategies and subsequent outcomes. Methods We searched PubMed, Web of Science, Scopus, and Google Scholar for articles related to keywords of myocarditis associated with scorpion envenomation up to May 1, 2022. Each article was carefully reviewed by two independent researchers. In case of disagreement for inclusion, we sought a third researcher opinion. Results A total of 703 cases from 30 case reports and 34 case series were included in our review. Myocarditis associated with scorpion envenomation was usually reported in children presenting with cardiopulmonary symptoms including pulmonary edema (60.7%) and shock or hypotension (45.8%). The most common ECG findings are sinus tachycardia (82%) followed by ST-T changes (64.6%). The management typically included inotropes (especially dobutamine), prazosin, diuretics, nitroglycerine and digoxin, when indicated. Mechanical ventilation was required in 36.7% of the patients. Mortality in confirmed scorpion-related myocarditis cases is estimated at 7.3%. Almost all survived cases showed rapid recovery and improvement in the left ventricular function. Conclusion Even though myocarditis associated with scorpion envenomation is rare, it remains a serious and in some of cases a fatal consequence of scorpion sting. In case of relative presentations, particularly in envenomed children, diagnosis of myocarditis should be considered. Early screening using serial cardiac markers and echocardiography can guide the treatment. Prompt treatment that focuses on cardiogenic shock and pulmonary edema usually results in a favorable outcome.